2017
DOI: 10.21873/anticanres.12098
|View full text |Cite
|
Sign up to set email alerts
|

Vinflunine in the Τreatment of Upper Tract Urothelial Carcinoma – Subgroup Analysis of an Observational Study

Abstract: Abstract. Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…Similar to the bladder cancer setting, second-line treatment of metastatic UTUC remains challenging. In a post hoc subgroup analysis of locally advanced or metastatic UC, vinflunine was reported to be as effective in UTUC as in bladder cancer progressing after cisplatin-based chemotherapy [203]. More importantly, a phase III RCT including 542 patients who received prior platinum-based chemotherapy for advanced UC showed that pembrolizumab could decrease the risk of death by almost 50% in those with UTUC (n = 75, 13.8%), although these results were borderline significant [204].…”
Section: Second-line Settingmentioning
confidence: 99%
“…Similar to the bladder cancer setting, second-line treatment of metastatic UTUC remains challenging. In a post hoc subgroup analysis of locally advanced or metastatic UC, vinflunine was reported to be as effective in UTUC as in bladder cancer progressing after cisplatin-based chemotherapy [203]. More importantly, a phase III RCT including 542 patients who received prior platinum-based chemotherapy for advanced UC showed that pembrolizumab could decrease the risk of death by almost 50% in those with UTUC (n = 75, 13.8%), although these results were borderline significant [204].…”
Section: Second-line Settingmentioning
confidence: 99%
“…In 2015, a prospective, observational study investigated the safety and efficacy of vinflunine in patients pre-treated with platinum-based chemotherapy [75]. Vinflunine was administered in the second line setting to 51 (66%) of the 77 patients.…”
Section: Chemotherapymentioning
confidence: 99%